PHYSICAL EDUCATION FOR YOUTH AND ADULT EDUCATION IN DEBATE (Fiep Bulletin - online, 2014)
Contribute to the development of physical education at the local level is the overall goal of this work, which includes, among others, encouraging new research and inform the public and academic teaching, enhance teacher in their educational activity, set up a new vista for the discurssão issues discussed. Under the title "The Physical Education for Youth and Adults in debate" Article Formulated as problem situation "assess whether or not the ability to teach effectively discipline in screen to learners of Youth and Adults forward their nesscessidades and requirements as well as to evaluate is currently being developed that discipline in state schools. As the structure of the work, it makes mention of the topics of education "body" in the context of physical education, physical education across the LDB, and the state decree 111/07 - CCE. This article was conducted through observations during the implementation stage of the compulsory curriculum in the State School Tancredo Neves as well as the Federal Center of Technological Education of Roraima. Realized even an interview with the director of the Department of Education Youth and Adult State Department of Education, Culture and Sports. Thus, this work is configured as an important source of research and consultation activities of labor Physical Educator of municipal and state physical education Roraima.
Keywords: Educaçao youth and adults; body education; health; goals; school education